Computational Dissection of Membrane Transport at a Microscopic Level. Issue 3 (March 2020) - Jiang, Tao; Wen, Po-Chao; Trebesch, Noah; Zhao, Zhiyu; Pant, Shashank; Kapoor, Karan; Shekhar, Mrinal; Tajkhorshid, Emad
Abstract : Membrane transporters are key gatekeeper proteins at cellular membranes that closely control the traffic of materials. Their function relies on structural rearrangements of varying degrees that facilitate substrate translocation across the membrane. Characterizing these functionally important molecular events at a microscopic level is key to our understanding of membrane transport, yet challenging to achieve experimentally. Recent advances in simulation technology and computing power have rendered molecular dynamics (MD) simulation a powerful biophysical tool to investigate a wide range of dynamical events spanning multiple spatial and temporal scales. Here, we review recent studies of diverse membrane transporters using computational methods, with an emphasis on highlighting the technical challenges, key lessons learned, and new opportunities to illuminate transporter structure and function. Highlights: Membrane transporters regulate a wide range of biochemical and physiological processes, many of them with direct implications in human health and disease. The high spatial and temporal resolutions offered by molecular dynamics (MD) simulations allow the investigation of a wide range of processes critical to the function of membrane transporters. MD simulations and related computational methods have become a powerful approach for in situ characterization of the structural and dynamical aspects of transporters within their natural membrane environment. Recent advances in computer algorithms, force fields, and computing power have resulted in a quantum leap in computational characterization of membrane transporters. Applications of integrative modeling techniques that incorporate experimental data from various sources into molecular models used by MD simulations open up new vistas to studying the functional cycles of transporters within their natural environment of a cell.